THE ROLE OF THE ISLAMIC FINANCE MODEL WITH ITS PHILOSOPHY, INSTRUMENTS AND CHARACTERISTIC FEATURES IN MITIGATING THE ECONOMIC IMPACTS OF THE COVID 19 - ARZOVA, SABRİ BURAK (ILAHIYAT BILIMLERI ARASTIRMA VAKFI, 2021)
COVID 19 has a devastating impact on the world economy. With the quarantine measures and the decrease in consumer and investor confidence, the economies of the country have shrunk. Businesses stopped their operations and unemployment increased. During the pandemic period, the shortcomings of traditional financing instruments emerged. In financing activities, environmental, social and economic factors should be organized in balance. Although the borrowing relationship in traditional financing activities contributes to environmental and social factors, it is not capable of establishing the necessary balance between these elements. The Islamic finance model can provide the economy, environment and social balance because of its risk sharing element and the characteristics of the principles of Islam. In this study, the effect of the Islamic financing model in the COVID 19 period and after the pandemic was examined. Then recommendations on the use of Islamic financing instruments against the economic effects of the pandemic were presented. Considering the literature review and the features of the Islamic financing model, it can be interpreted that the Islamic financing model can contribute to the world economy in the economic recovery during and after the COVID 19 process.
Keywords: Islamic Economy; Islamic Finance; COVID 19